1997
DOI: 10.1016/s0014-5793(97)01179-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myocytes and fibroblasts contain functional estrogen receptors1

Abstract: Gender-based differences found in cardiovascular diseases raise the possibility that estrogen may have direct effects on cardiac tissue. Therefore we investigated whether cardiac myocytes and fibroblasts express functional estrogen receptors. Immunofluorescence demonstrated estrogen receptor protein expression in both female and male rat cardiac myocytes and fibroblasts. Nuclear translocation of the estrogen receptor protein was observed after stimulation of cardiomyocytes with 17ß-estradiol (E 2 ). Cells tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
210
1
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(227 citation statements)
references
References 53 publications
(69 reference statements)
9
210
1
5
Order By: Relevance
“…While experimental studies in animals have demonstrated sex-related differences in LV systolic function and biochemistry induced by castration or hormone replacement 31,32 and that cardiac myocytes contain functional oestrogen receptors, 33 our study in patients 455 years of age indicates that hormone replacement therapy was not a factor in the observed sex-related difference in LV hypertrophy regression because the degree in absolute LV mass change was identical in women with or without hormone replacement. Further studies are needed to clarify the role of hormone replacement on LV hypertrophy.…”
Section: Potential Mechanismscontrasting
confidence: 50%
“…While experimental studies in animals have demonstrated sex-related differences in LV systolic function and biochemistry induced by castration or hormone replacement 31,32 and that cardiac myocytes contain functional oestrogen receptors, 33 our study in patients 455 years of age indicates that hormone replacement therapy was not a factor in the observed sex-related difference in LV hypertrophy regression because the degree in absolute LV mass change was identical in women with or without hormone replacement. Further studies are needed to clarify the role of hormone replacement on LV hypertrophy.…”
Section: Potential Mechanismscontrasting
confidence: 50%
“…A recent study describes coexpression of ERa and ERb protein in mouse mammary gland at di erent developmental stages (Saji et al, 2000). ERb protein has also been demonstrated to be expressed in rat cardiac myocytes and ®broblasts where ERa is also present (Grohe et al, 1997(Grohe et al, , 1998. ERb protein expression in hypothalamic parts of the rat brain appears to cooincide with ERa expression (Li et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of these differences is unclear but may be related to: (a) a reduced adaptive hypertrophic reserve in males (39); (b) the lower mitochondria respiratory and lysosomal enzyme activity in females (40); (c) a higher percentage of the V1 myosin isozyme, which is up-regulated by estrogen in females (41); and (d) the intrinsic gender-specific differences in cardiac muscle physiology and biochemistry (42). Furthermore, estrogen signaling through the adult myocyte estrogen receptor may contribute to gender differences in gene expression in pathological hypertrophy (43). Interestingly, in humans with congenital aortic stenosis and cardiac hypertrophy, there appears to be an overcompensation of myocardial contraction early on (44), which is similar to that described in mutant PLB females in this study.…”
Section: Discussionmentioning
confidence: 99%